The Implementation of Forensic Accounting to Enhance the Transparency of Financial Reports - Saputri, Adheriana Wida; Kurniawan, Widiar Onny; Putri, Chika Aulia (GREENOMIKA, 2025)
This study is a literature study that aims to examine the role of forensic accounting implementation in improving the transparency of financial reports. The main focus is to identify how the forensic approach can contribute to detecting fraud and strengthening the company's internal control system. The data in this study were obtained from various secondary sources such as scientific journal articles, books, research reports, and relevant case studies, which were selected purposively based on the suitability of the topic and the credibility of the source. The results of the study indicate that forensic accounting makes a significant contribution to improving the accuracy and accountability of financial information, especially through investigative audit techniques and forensic data analysis. This study recommends the integrity of forensic accounting in governance practices through improving human resource competency, utilizing technology, and strengthening ethics and reporting systems. The findings of this study are expected to be a reference for academics and practitioners in developing a more effective fraud prevention approach.